AccelSquare: acceleration of a movement at nonlinear areas estimator for teaching and learning processes - Alauddin, Aina Zulaikha; Shaharin, Nurrin Shafiya; Harun, Nurzalina; Sadikin, Zubaidah; Rathi, Sidik; Mohd Sidek, Nur Zafirah; Batcha, Siti Rahimah; Salim Nasir, Mohd Agos (Academica Press Solutions, 2024)
The current research is designed to assist the calculation of acceleration of a movement at non-linear area by using Discrete Least Square Method. Hence, the purpose of producing this prototype is due to the problem faced, which is the difficulty in calculating the acceleration of a movement due to the areas in UiTM Shah Alam that is in the form of rectangular domain and hilly terrain. AccelSquare works to calculate the acceleration of a movement at any non-linear areas using the data collected. It also works to utilize parametric equations in complex calculation. This prototype has its own value in terms of new idea development. It can be used by everyone to find an acceleration of any movement at any difficult areas, such as at any rectangular domain areas or hilly terrain. Next, based on the interfaces, AccelSquare can be used in learning and teaching processes which related to any calculation of acceleration in the subject syllabus. People who involve in the learning and teaching processes can be exposed to this prototype to facilitate the processes. However, since the process of calculating the acceleration manually can be very crucial and takes a long time, this system will be served as an alternative to the user as it will make the calculation process easier and more efficient. Other than that, AccelSquare helps the student from mathematics and physics background to understand better about acceleration in real life. This prototype can be upgraded for being used in any online platform.